Historia universal Siglo XXI. 26. La época de las revoluciones europeas, 1780-1848 / Louis Bergeron, François Furet y Reinhart Koselleck ; [traductor, Francisco Pérez Gutiérrez] - Furet, FrançoisKoselleck, ReinhartBergeron, Louis (1929-)
1° ed. (1976), 2° ed. (1978), 4° ed. (1979), 13° ed. (1989) | Bibliografía: p. 317-330. Índices